Aberrant mitochondrial RNA in the role of aging and aging associated diseases. Issue 2 (August 2015) - Chen, Yucai; Parker, W. Davis; Chen, Hongyi; Yang, Kunfang
Abstract Accumulations of mitochondrial DNA (mtDNA) mutations associated with aging are evident in multiple human tissues. The role of mtDNA mutations can be observed in an aging animal model such as homozygous knock-in PolgA mice, which have a large colonial expansion of mtDNA mutations. They develop reduced lifespan and premature onset of age-related phenotypes, that are also observed in clinical practice like mitochondrial aging acceleration with anti-retroviral therapy through clonal expansion of mtDNA mutations. These clonally expanded mtDNA mutations maintain transcription ability which could result in an accumulation of abnormal mitochondrial RNA (mtRNA) in the affected cells. Compensation-effect doctrine states that accumulated mtDNA mutations in the cell must reach a set threshold before they have a negative effect on cell function due to compensation effects from normal cellular mtDNA. In contrast to this theory, we suggest that an accumulation of aberrant mtRNA transcribed from mtDNA mutations negatively influences cellular function through complex internal and external mitochondrial pathways, and might be an important cause of aging and aging-associated diseases.